Grundsatzfragen der Rechtsetzung und Rechtsfindung : Referate und Diskussionen auf der Tagung der Vereinigung der Deutschen Staatsrechtslehrer in Münster vom 5. bis 8. Oktober 2011. - Calliess, Christian, 1964-; Lienbacher, Georg; Grzeszick, Bernd (De Gruyter, 2012)
This volume contains essays and discussions from the conference of the Association of German Constitutional Law Instructors held October,5 - 8, 2011 inMünster.
Keywords: Constitutional law -- Germany (West) -- Congresses.; Constitutional law -- Congresses.; LAW -- Constitutional.; LAW -- Public.; Constitutional law.; Germany (West); Electronic books.; Conference papers and proceedings.